TREM2‐induced activation of microglia contributes to synaptic resilience in non‐demented individuals with Alzheimer's neuropathology. (1st February 2022) - Fracassi, Anna; Marcatti, Michela; Woltjer, Randy L; Taglialatela, Giulio
Abstract: Background: The existence of individuals who remain cognitively intact despite presenting histopathological signs of Alzheimer's disease (AD), here referred to as "Non demented with AD neuropathology" (NDAN), suggests that some unknown mechanisms are triggered to resist cognitive impairment. Synaptic dysfunction has been identified as one of the major AD causes and it is established that microglia, attracted to plaques, engulf damaged synapses. In this context, exposed phosphatidylserine (ePS) represents a neuronal "eat‐me" signal involved in microglial‐mediated phagocytosis of damaged synapses. A possible candidate mediator of this process is represented by TREM2, a microglial surface receptor activated by ligands including PS. Based on TREM2 role in the scavenging function of microglia, we hypothesize that an efficient microglial phagocytosis of damaged synapses underlies synaptic resilience in NDAN, thus protecting from memory deficits. Method: Using immunofluorescence microscopy, a comparative study of human post‐mortem frontal cortices of aged‐matched individuals, AD and NDAN individuals has been performed. The distribution of activated microglia (IBA1 and IBA1/CD68 positive cells) and the expression of phagocytic microglia‐related proteins (TREM2 and DAP12) were evaluated. To test the efficacy of microglia in removing debris and damaged synapses, preservation of synapses around plaques was assessed using MAP2 and tubulin βIII as dendritic and axonal markers respectively, and PSD95 as a post synaptic marker. Furthermore, taking advantage of flow cytometry techniques, a study of the ePS using Annexin V assay has been performed. Result: Immunofluorescence analyses indicate higher microglial activation and TREM2 expression in NDAN individuals, as well as preserved axonal and dendritic structure around plaques vs . AD. High levels of PSD95 around NDAN plaques and the colocalization of PSD95 and CD68 may suggest a prompt removal of damaged synapses by hyperactive phagocytic microglia. Annexin V assay on synaptosomes isolated from aged‐matched, AD and NDAN individuals indicates changes in the ePS in NDAN individuals, confirming the engulfment of damaged synapses. Conclusion: Our results suggest a higher efficiency of TREM2‐induced phagocytic microglia in removing damaged synapses, underlying synaptic resilience in NDAN individuals.